Evaluation of Electronic-Based Government System Using The E-Government Maturity Model: Case Study of Bekasi City - Sintia Nursafitri; Riyanto Jayadi (Politeknik Ganesha Medan, 2023)
Since the primary purpose of government is to serve the community, providing high-quality public services is the primary outcome that is expected. As a result, the public sector must make adjustments for digitalization in light of recent technological advancements. An evaluation of the maturity of adopting an electronic-based government system must be done as part of the application for an electronic-based government system. The e-government maturity model framework, which comprises five stages, is used to evaluate the 4 domains, 8 aspects, and 47 indicators present in an electronic-based government system to determine the technological function's capabilities. 44 agencies that use an electronic-based government system were interviewed as part of the research technique, which also included a survey of the Bekasi City government environment. With a total index value obtained of 2.78 in 2022—a lower value than in the previous year—the city of Bekasi receives a Good predicate. In this study's measurement results, 16 indicators had the lowest index values, making them candidates for improvement suggestions for the Bekasi city government.